I Intervening Alokasi Belanja Pada Pengaruh Kinerja Keuangan Terhadap Pertumbuhan Ekonomi Pemerintah Daerah Jawa Tengah - syafnita (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
This study aims to examine and analyze the effec to flocal government financial performanceas measured by the independen ceratio, dependency ratio, degree of decentralization, PADeffectiveness ratio, degree of BUMD contribution and debt to income ratio on capitalexpenditure allocation and economic growth. As well as to examine and analyze the effect oflocal government financial performance as measured by the independence ratio,dependencyratio, degree of decentralization, PAD effectiveness ratio,degree of BUMD contribution anddebt to incomeratio on economic growth to mediated capital expenditure allocation.This research is a correlational study with acausal relationship, namely to examine the effectof regional financial performance on economic growth through the allocation of capitalexpenditures as an intervening variable. The sample in this study was 35 Regency/CityGovernments in Central Java. The data analysis technique used path analysis with SEM(Structural Equation Modeling).Theresults showed (1)Financial independence, financial dependence andThe degree of BUMD's contribution did not havea direct effect on the allocation of capitalexpenditures. The degree of decentralization, the effectiveness of PAD and the debt to incomeratio have a direct and significant effect on the allocation of capital expenditures. (2)Financial independence, degree of decentralization and effectiveness of PAD have a directeffect on economic growth. Financial dependence, degree of BUMD’s contribution, debt toincome ratio and capital expenditure allocation do not have a directand significant effect oneconomic growth. (3) Capital expenditur eallocation mediates the effect of the degree ofdecentralization, the effectiveness of PAD and the degree of BUMD's contribution oneconomic growth. However, the capital expenditure allocation does not mediate the effect offinancial independence, financial dependence and the debt to income ratio to economicgrowth